IMPLEMENTASI MODEL DICK AND CAREY PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Purnasari, Martina purnasari; Safwandy Nugraha, Mulyawan; Dedih, Ujang (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Islamic religious education, which aims to develop individuals into "insan kamil" (perfect human beings), is implemented through various models, designs, and curriculum development to ensure that the content and values are internalized by the learners. With this foundation, Islamic Religious Education (PAI) teachers strive to deliver engaging and enjoyable lessons to motivate students in their PAI studies. The Dick and Carey model is worth researching for its application at GIS Prima Insani Elementary School to explore how the implementation of this teaching model aligns with precision and suitability in enhancing motivation toward achieving learning objectives. The method employed is a case study with a qualitative approach. The Dick and Carey instructional model is well-suited for educational contexts due to its clear and systematic steps that emphasize learning outcomes. It is a systematic and organized model where each step is interconnected, providing a sense of direction and support for students. This structured approach ensures that students feel observed and supported, enhancing their commitment to follow the steps and achieve optimal learning outcomes. Thus, the Dick and Carey instructional model will be more familiar among educators and easy to implement across various educational levels.